Overview of Lung Cancer - Indira Medika, Ayu (Rifa'Institute, 2023)
The two main types of lung cancer are small cell carcinoma and non-small cell carcinoma. Lung cancer is a primary bronchogenic carcinoma. Patients who are diagnosed with lung cancer typically exhibit symptoms like hemoptysis, dyspnea, chronic cough, chest pain, or weight loss. Since the onset of symptoms typically indicates that a patient's stage has already progressed, screening with low-dose chest CT (LDCT) exams is advised for high-risk patients. Cytology and core biopsy specimens are the main sources of the diagnosis for these patients. Staging, histology, genetic, and immunotherapy biomarker tests form the basis of the treatment. The most often used pharmacological therapies include radiotherapy, adjuvant platinum-based chemotherapy, surgery, which might involve mediastinal lymph node dissection or lymph node sampling, as well as total removal of the tumor (typically stages I and II). Currently, meanwhile, immunotherapy is the most advanced form of treatment for NSCLC that is oncogenic driver negative